Empowering Prospective Brides and Grooms through Qaryah Thayyibah Based Premarital Nutrition Education at KUA Kramatwatu - Nay Lufar; Lina Marliana; Iis Ismawati; Suwandi (ServeInnovate: Journal of Applied Community Engagement (SJACE), 2026)
Stunting in Indonesia remains a complex public health challenge, with poor preconception nutritional status, particularly among prospective mothers, being one of the contributing factors to its high prevalence. Adequate nutrition before pregnancy plays a crucial role in determining pregnancy outcomes and supporting optimal child growth and development. However, this aspect has not yet been systematically integrated into premarital education programs at the Office of Religious Affairs (KUA). In Kramatwatu Subdistrict, Serang Regency, the prevalence of early marriage remains relatively high, while existing premarital guidance has not sufficiently addressed key issues such as nutrition, reproductive health, and household food security. This community service program aimed to provide integrated premarital education through a community-based approach grounded in Qaryah Thayyibah values, which emphasize family resilience in spiritual, social, and health dimensions. The program was implemented through the development of integrated educational modules, participatory thematic classes for prospective brides and grooms, and the provision of educational media, including leaflets, posters, and short videos. The results showed a substantial improvement in participants’ knowledge of preconception nutrition, reproductive health, household food security, and stunting prevention. Pre-test and post-test evaluations revealed an average score increase of 24.80 points, indicating the effectiveness of the intervention in enhancing participants’ understanding of these key topics.